Mengembangkan Kemampuan Pemahaman Konsep Peserta Didik Melalui Pembelajaran Berbasis VCD - Farida, Farida (Universitas Islam Raden Intan Lampung, INDONESIA, 2015)
There are several factors that with low learning outcomes of learners, the most important is the low interest of learners to follow the lesson well and earnestly. Lack of strong motivation to be one cause of low interest learners learners. This study aims to improve the ability to understand the mathematical concepts of the subject matter kesebangunan. The benefits of this research is to provide input in choosing a varied learning model that can improve the learning outcomes of learners mathematics as well as information materials for other researchers. The research method used is experimental research with right t test with population class IX SMP Negeri 3 Bandar Lampung. The results showed that learning mathematics with VCD media learning on the ability of understanding the concept of class IX students SMP Negeri 3 Bandar Lampung semester I on the subject matter kesebangunan more effective than conventional learning, it is seen from the ability to understand the concept of learners better than conventional learning . Thus learning mathematics with VCD media learning on the subject matter kesebangunan can be used as an alternative method in learning in order to increase the variety of teaching methods in the effort to train the skills of reasoning and communication of learners and improve learning outcomes of learners.